(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper aims to identify the role of Artificial Intelligence (AI) in learning grammar. It compares the traditional methods of learning grammar (i.e., learning with books, articles, online lectures, etc.) with the trend of ‘Chat GPT’. The study tries to answer the following two questions: 1) Which kind of grammar learning sources can provide the students with the basic information related to a specific grammatical topic? 2) What areas of grammar does ChatGPT serve in the learning process? To answer the questions, 44 English major students are given a pre-post sheet with a time interval of almost fifteen days. They are exposed to either the traditional methods of learning grammar or those provided by the AI platform Chat GPT. Their produced grammar knowledge is analyzed based on predetermined criteria. The hypothesis defended is that traditional methods provide less effective grammar knowledge compared to that provided by Chat GPT which is rather real-life knowledge tailored to the students’ needs. Students may consequently achieve learning due to the interactive learning nature of using Chat GPT.